Cushing's syndrome caused by an occult source: difficulties in diagnosis and management. - Grossman, AB; Kelly, P; Rockall, A; Bhattacharya, S; McNicol, A; Barwick, T; Balwick, T (2006)
BACKGROUND: A 24-year-old woman presented with a 12.5 kg weight gain over 6 months (mostly abdominal), hirsutism, acne, ankle edema, polydipsia, nocturia, back pain, pigmentation, poor libido and lightened menses to our hospital in May 1986. She had been treated for the previous 2 years with furosemide and spironolactone for peripheral edema, and had stopped the combined oral contraceptive 2 months previously. She did not take tobacco, recreational drugs or alcohol. Upon physical examination she was grossly Cushingoid with florid clinical manifestations. INVESTIGATIONS: Serum potassium and bicarbonate, circadian rhythm of cortisol, low-dose and high-dose dexamethasone suppression tests, plasma adrenocorticotropic hormone (ACTH), corticotropin releasing-hormone stimulation test, CT scan of the pituitary, plain chest radiology, CT scan of the chest and abdomen, trans-sphenoidal pituitary biopsy and histology, CT scan and MRI of the thorax, MRI of the pituitary, octreotide scintigraphy, gastroscopy, colonoscopy, gut peptides, tumor markers, urine 5-hydroxyl-indole-acetic acid, resection, histology, immunocytochemistry and in situ hybridization. DIAGNOSIS: Occult ectopic ACTH syndrome from a presumed appendiceal neuroendocrine tumor. The tumor was only identified some 20 years from initial presentation. MANAGEMENT: Adrenolytic therapy before bilateral adrenalectomy to cure Cushing's syndrome, glucocorticoid and mineralocorticoid replacement therapy, and then repeated surveillance over 20 years to locate the ectopic source of ACTH. This was finally identified by CT scan and excised at laparotomy.